Real-time dynamic 3-T MRI assessment of spine kinematics: a feasibility study utilizing three different fast pulse sequences. (January 2021) - Walter, William R; Alizai, Hamza; Bruno, Mary; Portugal, Salvador; Burke, Christopher J
Background: Half-Fourier acquisition single-shot turbo spin-echo (HASTE), continuous radial gradient-echo (GRE), and True FISP allow real-time dynamic assessment of the spine. Purpose: To evaluate the feasibility of adding dynamic sequences to routine spine magnetic resonance imaging (MRI) for assessment of spondylolisthesis. Material and Methods: Retrospective review was performed of patients referred for dynamic MRI of the cervical or lumbar spine between January 2017 and 2018 who had flexion-extension radiographs within two months of MRI. Exclusion criteria were: incomplete imaging; spinal hardware; and inability to tolerate dynamic examination. Blinded, independent review by two board-certified musculoskeletal radiologists was performed to assess for spondylolisthesis (>3 mm translation); consensus review of dynamic radiographs served as the gold standard. Cervical spinal cord effacement was assessed. Inter-reader agreement and radiographic concordance was calculated for each sequence. Results: Twenty-one patients were included (8 men, 13 women; mean age 47.9 ± 16.5 years). Five had MRI of the cervical spine and 16 had MRI of the lumbar spine. Mean acquisition time was 18.4 ± 1.7 min with dynamic sequences in the range of 58–77 s. HASTE and True FISP had the highest inter-reader reproducibility (κ = 0.88). Reproducibility was better for the lumbar spine (κ = 0.94) than the cervical spine (κ = 0.28). Sensitivity of sequences for spondylolisthesis was in the range of 68.8%–78.6%. All three sequences had high accuracy levels: ≥90.5% averaged across the cervical and lumbar spine. Cervical cord effacement was observed during dynamic MRI in two cases (100% agreement). Conclusion: Real-time dynamic MRI sequences added to spine MRI protocols provide reliable and accurate assessment of cervical and lumbar spine spondylolisthesis during flexion and extension.